Menyibak Kekerasan Simbolik Orientalisme - Iswahyudi Iswahyudi (Universitas Islam Negeri Mataram, 2007)
Recent order of world civilization seems to be constructed by Western civilization through project of orientalism which assumes East as the passive receiver of anything West actively offer; East is considered uncivilized, primitive, and dominated by myth and superstition. Based on the assumptions, West wants to inject modernity awareness into East cognitive sphere. But, East finds the want as a West tricky way to dominate East, a new kind of colonialism, and a hegemony. West hegemony covered under orientalism—to use Pierre Boudeau’s term—is a kind of symbolic violence. The term refers to a violence insulted smoothly; it is differed from domination which refers more to physical violence. Orientalism symbolic violence can be traced through orientalists’ works on East that are scientifically and massively published. The violence should be wisely responded by East through creating balance discourse based on scientific and intuitive capabilities. Recent order of world civilization seems to be constructed by Western civilization through project of orientalism which assumes East as the passive receiver of anything West actively offer; East is considered uncivilized, primitive, and dominated by myth and superstition. Based on the assumptions, West wants to inject modernity awareness into East cognitive sphere. But, East finds the want as a West tricky way to dominate East, a new kind of colonialism, and a hegemony. West hegemony covered under orientalism—to use Pierre Boudeau’s term—is a kind of symbolic violence. The term refers to a violence insulted smoothly; it is differed from domination which refers more to physical violence. Orientalism symbolic violence can be traced through orientalists’ works on East that are scientifically and massively published. The violence should be wisely responded by East through creating balance discourse based on scientific and intuitive capabilities.